Effect of Aerobic Interval Training on Expression of Twist and Vimentin and the Rate of Tumor Volume in Mice with Breast Cancer - S Gholamian (Babol University of Medical Sciences, 2020)
BACKGROUND AND OBJECTIVE: Many deaths from cancer are due to metastases, a process which involves the epithelial-mesenchymal transition (EMT). On the other hand, regular exercise plays an important role in inhibiting the progression of breast cancer. Therefore, the purpose of this study was to investigate the influence aerobic interval training on expression of mesenchymal biomarkers, and tumor volume in mice with breast cancer. METHODS: In this experimental study, Thirty-two female BALB/c mice, aged 3-5 weeks (17±1g) were used. The mice were allocated to four groups: Exercise Tumor, Exercise (aerobic Interval training was performed six weeks (40 minutes) before and four weeks (30 minutes) after the induction of carcinoma with active recovery), Rest Tumor, Rest (Control- without exercise), Rest, Tumor, Exercise, (four weeks after the induction of carcinoma) and Exercise, Tumor, Rest (six weeks before the induction of carcinoma). The real-time PCR method was used to evaluate the expression of Vimentin and Twist. FINDINGS: The results of present study demonstrated that tumor tissue Vimentin expression in the Exercise Tumor Exercise (223.0±0.073) group decreased significantly (p= 0.0001), Also, the expression of Twist gene was significantly reduced in Exercise Tumor Exercise group (0.24±0.227) compared to control group (p=0.008). A significant decrease in tumor volume was observed in both RTE and ETE groups compared to the control group (RTR) (p = 0.0001). CONCLUSION: Based on the results of this study, a period of interval aerobic training can decrease the expression of Vimentin، Twist and decrease the tumor volume ratio.